2022
DOI: 10.1016/j.jad.2021.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of probable depression and anxiety during the COVID-19 pandemic in seven countries: Longitudinal evidence from the European COvid Survey (ECOS)

Abstract: Background Our aim was to present data on the prevalence of probable depression and anxiety and to determine their correlates during the COVID-19 pandemic in seven European countries using a longitudinal approach. Methods Longitudinal data (wave 4 in November 2020: n= 7,115; wave 5 in January 2021: n=7,068; wave 6 in April 2021: n=7,204) were taken from the European COvid Survey (ECOS), a representative sample of non-institutionalized inhabitants from Germany, United Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 53 publications
6
47
1
3
Order By: Relevance
“…Only a few national (and, in the light of available knowledge, also foreign) papers already published deal with cross-sectional studies repeated during the pandemic [ 34 ]. There are also a few very unique longitudinal studies [ 5 , 32 ]. International projects, the results of which are just beginning to be announced, have to be considered a valuable initiative [ 23 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few national (and, in the light of available knowledge, also foreign) papers already published deal with cross-sectional studies repeated during the pandemic [ 34 ]. There are also a few very unique longitudinal studies [ 5 , 32 ]. International projects, the results of which are just beginning to be announced, have to be considered a valuable initiative [ 23 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of the above components of sexual life were analyzed in relation to the pandemic period [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The contributions came from various countries, including Poland [ 19 , 25 , 29 , 30 , 31 , 32 , 33 , 34 ], sometimes based on multi-country projects [ 8 , 23 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, data from the Health National Survey in 2017 indicated that in the sample aged 15–24, 1.1% of men and 3% of women suffered from anxiety, while in the sample aged 25–34, this percentage increased to 3.6% in men and 5.9% in women ( 32 ). During the COVID-19 pandemic, an increase in anxiety has been observed in the youth population ( 33 35 ). Racine et al ( 36 ) have concluded, in a recent meta-analysis of 29 studies including 80,879 youths globally, that the prevalence of anxiety symptoms during the pandemic has doubled, with 1 in 5 youths experiencing clinically elevated anxiety symptoms.…”
Section: Gender Differences In Anxiety In the Emerging Adulthoodmentioning
confidence: 99%
“…This is because young adults are more precarious, less resilient and less socially supportive, and the disruption brought on by the COVID-19 epidemic exacerbates loneliness and financial distress among young adults, bringing more prevalent depressive symptoms ( Jinhee et al, 2021 ; Varma et al, 2021 ). Specifically, the reasons for this consequence mainly include: 1)Young adults are more vulnerable to social support and economic status than other groups, and are more difficult to cope with the impact of the epidemic, especially inflation and employment pressure ( Hajek et al, 2022 ; Hsiang et al, 2020 ; Varma et al, 2021 ); 2)Young adults tend to have high levels of attention to the outbreak but less mature cognition than older adults ( Wierenga et al, 2021 ), and are more likely to have negative expectations about the prospect for the epidemic and socioeconomic development, which increases their likelihood of developing depressive symptoms ( Amicucci et al, 2021 ; Bucciarelli et al, 2022 ; Gallagher et al, 2021 ; I & K, 2021 ; She et al, 2022 ); 3)Many young adults in Hubei Province participated in volunteer work in combatting COVID-19 epidemic, concerns about infection during frontline work may make them depressed, and the experience of contracting COVID-19 may also increase their probability of developing depressive symptoms ( Balakrishnan et al, 2022 ; Bucciarelli et al, 2022 ; Pera, 2020 ; Yu et al, 2021 ); and 4)Young adults have higher cross-regional mobility due to work or schooling, as the residents of the earliest eye of epidemic storm, they may experience more discrimination and distrust after order is restored in the post-pandemic period, which likely to worsen their social relationships and cause loneliness, stress and depression ( Espinoza & Hernandez, 2022 ; Siu, 2008b ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cognition and experience of the COVID-19 epidemic may have a negative impact on the psychological state of young adults and even lead to depression during the outbreak, and this effect may continue into the post-epidemic period ( Ebrahimi et al, 2022 ; Gallagher et al, 2021 ). In addition, social connections, employment, and financial stress may exacerbate depressive symptoms in young adults in the post-pandemic period ( Hajek et al, 2022 ; I & K, 2021 ; Jinhee et al, 2021 ). In the post-epidemic period, paying attention to the psychological status and demands of the young adults, strengthening psychological intervention and providing policy support can help the young adults participate in economic recovery and reconstruction.…”
Section: Introductionmentioning
confidence: 99%